Chained Approach vs Contingent Valuation for Estimating the Value of Risk Reduction - Sara Olofsson; Ulf-G. Gerdtham; Lars Hultkrantz; Ulf Persson (Lund University, School of Economics and Management, Department of Economics, 2016)
To decide how much resources to spend on reducing mortality risk, governmental agencies in several countries turn to the value of a statistical life (VSL). VSL has been shown to vary depending on the size of the risk reduction, which indicates that WTP does not increase near-proportional in relation to risk reduction as suggested by standard economic theory. Chained approach (CA) is a stated preference method that was designed to deal with this problem. The objective of this study was to compare CA to the more traditional approach contingent valuation (CV). Data was collected from 500 individuals in the Swedish adult general population using two web-based questionnaires, whereof one based on CA and the other on the CV method. Despite the two different ways of deriving the estimates, the methods showed similar results. The CV result showed scale insensitivity with respect to the size of the risk reduction and disease duration and resulted in more zero and protest response. The CA result did also vary depending on the procedure used, but not when chaining on individual estimates. The CA result was also found to be more sensitive to disease duration and severity. This study provides support for the validity of studies of the WTP for a risk reduction. It also shows that CA is associated with encouraging features for the valuation of non-fatal road traffic accidents, but the result does not support the use of one method over the other.
Keywords: D61; D80; I18; J17; 330; contingent valuation; chained approach; scale sensitivity; risk reduction; willingness-to-pay